2002
DOI: 10.1128/jvi.76.24.12435-12447.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transcription Profile of Adeno-Associated Virus Type 5 Reveals a Number of Unique Features Compared to Previously Characterized Adeno-Associated Viruses

Abstract: We report the initial characterization of adeno-associated virus type 5 (AAV5) RNAs generated following viral infection and the construction of a replicating infectious clone of AAV5. While the basic transcription profile of AAV5 was similar to that of AAV2, there were also significant differences. Mapping of the AAV5 transcripts demonstrated an efficient transcription initiation site within the AAV5 inverted terminal repeat (ITR), and mapping of the AAV5 intron revealed that it is considerably smaller than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
122
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(126 citation statements)
references
References 45 publications
4
122
0
Order By: Relevance
“…The BAAV genome had the highest homology with AAV-5, and we have demonstrated that the Rep proteins of BAAV can be used to package an AAV-5 genome. Another unique feature of AAV-5, a dimer of polyadenylation sites at the 3Ј end of the rep78 ORF, is also conserved in BAAV (data not shown) (25). At the protein level, BAAV Rep78 and VP1 have the highest homology with AAV-5 Rep78 and AAV-4 VP1, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The BAAV genome had the highest homology with AAV-5, and we have demonstrated that the Rep proteins of BAAV can be used to package an AAV-5 genome. Another unique feature of AAV-5, a dimer of polyadenylation sites at the 3Ј end of the rep78 ORF, is also conserved in BAAV (data not shown) (25). At the protein level, BAAV Rep78 and VP1 have the highest homology with AAV-5 Rep78 and AAV-4 VP1, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…A drawback of this uniqueness is that the AAV-5 genotype is hard to pseudotype, which hampered analyses of the contribution of AAV-5 ITRs to vector function in the past and represented a hurdle we had to overcome in the present study (see Results). AAV-5 ITRs are also the only candidates other than AAV-2 for which an intrinsic promoter activity was reported, a property that could be exploited by flanking vector DNAs with AAV-5 ITRs, as was previously suggested (17,52).…”
mentioning
confidence: 96%
“…However, as shown in Fig. 1B, and as we have shown previously (7,8,(10)(11)(12), substantial levels of a Rep40-like protein product are generated during both AAV5 and goat AAV infections of 293 cells (Fig. 1B, lanes 1 and 2), despite the relatively low levels (Ͻ5%) of splicing from upstream transcripts (Fig.…”
mentioning
confidence: 92%
“…Thus, these viruses would not be expected to generate significant quantities of Rep40. However, immunoblot analyses have consistently demonstrated the presence of significant levels of a Rep40-like (but not a Rep 68-like) protein during AAV5 and goat AAV coinfection with adenovirus, as well as during transient transfection (7,8,11). This suggested that AAV5 may generate a Rep40-like protein using a mechanism distinct from the alternative splicing utilized by AAV2.…”
mentioning
confidence: 99%
See 1 more Smart Citation